2009
DOI: 10.1002/dc.21095
|View full text |Cite
|
Sign up to set email alerts
|

Cell survival and apoptosis‐related molecules in cancer cells in effusions: A comprehensive review

Abstract: Spreading of cancer cells to effusions is a manifestation of advanced disease, for which the chances of achieving cure using conventional treatment are low. This emphasizes both the importance of improving early detection and the need for developing targeted therapy modes. Such approaches should be based on characterization of the antiapoptotic, survival and drug resistance mechanisms of the metastatic cells in addition to analysis of the primary tumor. This review presents current knowledge regarding the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 165 publications
(160 reference statements)
0
10
0
Order By: Relevance
“…The inhibition of NF-κB by NO donors was found to lead to the repression of anti-apoptotic target genes including YY1 , further illustrating YY1 as a direct target gene of NF-κB. 10,13 Likewise, reports by Karin et al, 36 Hongo et al, 37 and Kleinberg et al 38 further corroborated that NF-κB regulates the activation of YY1 and also other genes such as the X-linked inhibitor of apoptosis protein (XIAP) and the B-cell lymphoma-extra large (Bcl-xL) through direct targeting.…”
Section: Indirect Regulation Of Emt By Yy1 Through the Nf-κb/snamentioning
confidence: 88%
“…The inhibition of NF-κB by NO donors was found to lead to the repression of anti-apoptotic target genes including YY1 , further illustrating YY1 as a direct target gene of NF-κB. 10,13 Likewise, reports by Karin et al, 36 Hongo et al, 37 and Kleinberg et al 38 further corroborated that NF-κB regulates the activation of YY1 and also other genes such as the X-linked inhibitor of apoptosis protein (XIAP) and the B-cell lymphoma-extra large (Bcl-xL) through direct targeting.…”
Section: Indirect Regulation Of Emt By Yy1 Through the Nf-κb/snamentioning
confidence: 88%
“…in accordance with the results for Bax/Bcl-2, HSP47 overexpression also resulted in increased expression of cleaved caspase-7/-8/-9 and PARP. Caspase-8 and caspase-9 both play a role in the extrinsic apoptotic pathway and the intrinsic mitochondrial apoptotic pathway, respectively, given that both of them can activate downstream caspase family proteins, such as caspase-7 (44,49,50). Therefore, it appears that HSP47 induces apoptosis via both the extrinsic and the intrinsic mitochondrial apoptosis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic pathway releases cytochrome c to form apoptosome to activate caspase 9/3 in the cells (Ouyang et al, ), whereas extrinsic pathway is triggered by binding of Fas and plasma membrane death receptor with its extracellular ligand Fas‐L to activate caspase 8/3. Thus, recently, apoptosis is an important target for cancer therapy (Kleinberg and Davidson, ; Ouyang et al, ). In the current study, GBA showed cytotoxicity in wild EGFR type H460 and A549 cells better than other mutant type PC‐9 and HCC827 NSCLC cells, implying EGFR may mediate the cytotoxicity of GBA in wild EGFR type H460 and A549 cells.…”
Section: Discussionmentioning
confidence: 99%